A native with a taste for the exotic: weeds and pasture provide year‐round habitat for Nysius vinitor (Hemiptera: Orsillidae) across Australia, with implications for area‐wide management. Issue 2 (5th March 2019) - Parry, Hazel R; Marcora, Anna; Macfadyen, Sarina; Hopkinson, Jamie; Hulthen, Andrew D; Neave, Mick; Bianchi, Felix J J A; Franzmann, Bernard A; Lloyd, Richard J; Miles, Melina; Zalucki, Myron P; Schellhorn, Nancy A
Abstract: While pest management tends to focus on pests that are already present in crops, non‐crop hosts may play a crucial role in supporting pest populations outside the crop growing season. Non‐crop hosts may allow pest populations to persist throughout the year, build‐up and colonise crops after emergence. Here, we assess the hosts of the Rutherglen bug, Nysius vinitor Bergroth, which is a polyphagous native insect pest of growing economic importance in Australia. We conducted a literature review on the occurrence of N. vinitor on crop and non‐crop hosts and analysed field survey data on N. vinitor abundance from two independent field studies in three agricultural regions of Australia. We differentiated between juvenile (nymph) and adult stages to consider the function of plants as reproduction sites. The literature review resulted in reports of N. vinitor on 44 crop species from 18 plant families. Pigweed Portulaca oleracea and capeweed Arctotheca calendula were the most cited weed hosts. In the field study, N. vinitor was primarily found on exotic weeds and grasses within pastures, Lucerne and degraded native vegetation remnants. While N. vinitor was found on a total of 16 weed plant families, juvenile stages of N. vinitor were most often observed on fleabane ( Conyza spp.), goosefoot Chenopodium pumilio (Amaranthaceae) and plants of the Asteraceae family, indicating that these are important host plants for N. vinitor reproduction. Grasses appear to be an important but understudied host plant group; citations in the literature do not reflect the extent to which N. vinitor was found on grasses in the field. In contrast, the field survey indicated that very few native plant species supported N. vinitor, which was consistent across regions and confirms findings from the literature review. Our findings suggest that exotic weeds and grasses (but not native plants) play a key role in supporting N. vinitor populations in Australian agricultural landscapes. Reducing exotic weeds in pastures and non‐crop habitats may limit breeding opportunities of N. vinitor and may be an important component in the area‐wide management of this polyphagous pest.